Supernatural Phenomena in Synge’s Riders to the Sea - Hidayati Hidayati (Proceedings of AICS - Social Sciences, 2017)
The focus of the study is to analyze the supernatural phenomena experienced by a family on Aran Island located on the west coast of Ireland. The person directly involved with the supernatural phenomena is Maurya, the protagonist of the drama, having lost all of her male family members. By the time this story begins, the second last son, is declared lost and finally found dead on the sea. After that her youngest son goes to the bazaar in the Mainland to sell horses but he never returns. These supernatural phenomena with various forms emerge from the span of these two events. There is a strong belief in supernaturalism among the people of Aran Island and this makes supernaturalism a significant aspect of the whole storyline. The research method used is Descriptive Qualitative with a focus on library research with the ground that descriptive qualitative is appropriately used to study the social phenomena where people make various senses of their life experiences. The result shows that the supernatural phenomena appear in varied forms: Mystery behind the death of Michael, Supernatural vision of Maurya, Foresightof Mauryaand Supernatural nuance in the title.  Keywords: supernaturalism, mystery, vision.